Memberdayakan Pendidik melalui Kepemimpinan Transformasional: Peran Kepala Madrasah dalam Meningkatkan Efektivitas Guru - Nailan, Akhmaliah Siti; Nugraha, Mulyawan Safwandy (FONDATIA, 2024)
The motivation for the study was the importance of transformational leadership in developing teachers' work at MIN Bandung. However, there is little research on the contribution of this type of leadership in Islamic education. The purpose of this study is to examine the responsibilities of school/madrasah leaders in improving teacher performance. This study used a quantitative comparative method. The research sample consisted of 21 teachers from MIN Bandung, and information was gathered through a Likert scale-based questionnaire that measured teachers' perceptions of transformational leadership and teachers' roles, and the relationship between variables. Based on the research, the findings indicate that the transformational leadership of school leaders in MIN Bandung is in the best category, and is positively and significantly related to improving teacher performance. It can be concluded that transformational leadership is essential to establish supportive working conditions, which can motivate and encourage teachers to be more creative and responsible to ensure the quality of academic coaching in schools.